STRATEGIC RESPONSE AND ITS ROLE IN ENHANCING THE ORGANIZATIONAL PRESTIGE (AN ANALYTICAL RESEARCH IN WASIT UNIVERSITY PRESIDENCY) - Shehenaz Fadhil AHMED; Buraq Talib ABDULJABBAR; ISRAA SHANAN THABIT (American Journals, 2023)
The current research aims to clarify the strategic response role in enhancing the organization prestige. The research was applied in Wasit University presidency. The research sample was chosen from (departments officials, their assistants, and officials of divisions and units) whose number is (43). The researchers used the analytical descriptive approach, and for the purposes of data collection, they developed a questionnaire that covered the research variables and their sub-dimensions, which were interpreted in 37 paragraphs. Many statistical methods were adopted such as (the arithmetic mean, the standard deviation, the Spearman correlation coefficient, the F test, and simple linear regression analysis). The ready-made statistical program SPSS. 28 was used to test the main hypothesis validity, which states that "the strategic response has a statistically significant effect on the organizational prestige". The research has reached out to prove the main hypothesis validity at the macro level and at the level of sub-dimensions as a whole.
Keywords: Strategic response, organizational prestige, strategic sensing, strategic flexibility.